Reconceptualizing Translation – Some Chinese Endeavours - Cheung, Martha (Meta, 2011)
This article examines, in the context of Chinese discourse on translation, a phenomenon observable in translation studies in the Euro-American world in the last few decades, namely the reconceptualization of translation. Based on historical research, the article shows that in different periods in the history of translation in China, there have been repeated attempts to respond to the realities of translation of the time by offering new (as opposed to established) conceptualizations and explications of translation (fanyi 翻譯). What these conceptualizations are will be analyzed with reference to a number of texts taken from different periods of Chinese discourse on translation. The article will also explore the connections amongst these conceptualizations and show how a mental frame could be produced that could serve as the blueprint of a project of international collaborative research, one in which ethnocentric bias of all kinds will have no place. In the last section of the article, the author will continue the tradition of reconceptualizing translation by offering one more definition of fanyi 翻譯.